Flutuações na abundância e no tamanho populacional de Eulaema nigrita Lepeletier (Hymenoptera, Apidae) no Cerrado - Castro, Ana Caroline Fagundes de (2019)
The Cerrado presents a variety of vegetational mosaics and there is few information comparing the abundance of Euglossini bees in the different physiognomies types of this biome. As one of the most abundant species in Cerrado physiognomies and being easily attracted by aromatic traps, Eulaema nigrita can be considered a good model for population studies aiming to test the effect of seasonality and heterogeneity of Cerrado environments on species. The objective of this study was to evaluate: (a) if the seasonality and diversity of Cerrado plant formations affect the abundance of El. nigrita males; (b) the population sizes of this species in the dry and rainy seasons; (c) whether the likelihood of recapture, a parameter used in population estimates, depends on the number of marked individuals, and whether this relation varies between the dry and rainy seasons; and (d) the influence of the number of sampling points on the amount of recaptures between the dry and rainy seasons. The study was conducted at Panga Ecological Station, in Uberlândia - MG, a conservation unit that has forest, savanna and field formations. The males of El. nigrita were sampled simultaneously by aromatic traps at four sites: 1- Gallery Forest (GF); Cerradão (CE); 3 – Cerrado Typical Restricted Sense (CT); and 4- Cerrado Drain Restricted Sense (CD). Eight collection sessions were conducted, four in the rainy season (between December/2017 and March/2018) and four in the dry season (between June/2018 and August/2018). In each session the samples were made in 4 consecutive days, in the period of 8 AM to 1 PM. During these sessions, males collected at the GF site were marked by a non-lethal method, released and recaptured in the traps located at all sampling sites. The Jolly-Seber method was applied for population estimates (b), analysis of variance (ANOVA) to respond objectives (a) and (d), and logistic regressions to respond objective (c). The abundances and populations were higher in the rainy season, with the former varying according to physiognomies. Regarding the recaptures, there was a greater number of recaptured individuals with the increase of the recapture sites, as well as a relation between the number of captures and recaptures in the dry season. The results presented here reinforce the importance of the conservation of the different Cerrado physiognomies for El. nigrita and the need for a greater effort to recapture individuals in studies that aim to make population estimates of this species.